2011
DOI: 10.1093/jxb/err285
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of barley betaglucanless mutants demonstrates a unique role for CslF6 in (1,3;1,4)-β-D-glucan biosynthesis

Abstract: (1,3;1,4)-β-D-glucans (mixed-linkage glucans) are found in tissues of members of the Poaceae (grasses), and are particularly high in barley (Hordeum vulgare) grains. The present study describes the isolation of three independent (1,3;1,4)-β-D-glucanless (betaglucanless; bgl) mutants of barley which completely lack (1,3;1,4)-β-D-glucan in all the tissues tested. The bgl phenotype cosegregates with the cellulose synthase like HvCslF6 gene on chromosome arm 7HL. Each of the bgl mutants has a single nucleotide sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
118
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(127 citation statements)
references
References 46 publications
8
118
0
1
Order By: Relevance
“…According to previous reports, the β-glucan content in oat grains appears to be controlled by genes with predominant additive effects (Cervantes- Martinez et al, 2001). In barley, a diploid species, it was suggested that only the gene HvCslF6 has high influence on the synthesis of β-glucans in the grains (Taketa et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…According to previous reports, the β-glucan content in oat grains appears to be controlled by genes with predominant additive effects (Cervantes- Martinez et al, 2001). In barley, a diploid species, it was suggested that only the gene HvCslF6 has high influence on the synthesis of β-glucans in the grains (Taketa et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to employing the N. benthamiana leaf system to view the subcellular distribution of CSLF6/H1, we also sought to use it as a functional assay system (Taketa et al, 2012;Vega-Sánchez et al, 2012). Given the abnormal accumulation pattern of VENUS-CSLF6 in large aggregates at the periphery of infiltrated epidermal cells (Supplemental Figure 8), we questioned whether the fluorescently tagged CSLF6 protein was catalytically active.…”
Section: Functional Analysis Of Cslf6 and Cslh1 Proteins In The N Bementioning
confidence: 99%
“…Protein gel blot analysis confirmed that the intact ;125-kD VENUS-CSLF6 fusion protein accumulated to detectable levels in these leaves ( Figure 10A). Upon digestion of AIR samples with lichenase, a MLG-specific endohydrolase, the diagnostic oligosaccharides of grass MLGs, the tri-(G4G3G R ) and the tetra-(G4G4G3G R ) saccharides, were detected ( Figure 10B), indicating that the VENUStagged CSLF6, like its untagged counterpart (Taketa et al, 2012;Vega-Sánchez et al, 2012), is active in N. benthamiana leaves.…”
Section: Functional Analysis Of Cslf6 and Cslh1 Proteins In The N Bementioning
confidence: 99%
See 2 more Smart Citations